2014
DOI: 10.1103/physrevb.90.035443
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Raman enhancement by two-dimensional materials: Applications for graphene-enhanced Raman spectroscopy

Abstract: We propose a third-order time-dependent perturbation theory approach to describe the chemical surfaceenhanced Raman spectroscopy of molecules interacting with two-dimensional (2D) surfaces such as an ideal 2D metal and graphene, which are both 2D metallic monolayers. A detailed analysis is performed for all the possible scattering processes involving both electrons and holes and considering the different time orderings for the electron-photon and electron-phonon interactions. We show that for ideal 2D metals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 26 publications
5
57
0
Order By: Relevance
“…Raman enhancement based on chemical mechanism in graphene has been explained as a resonant Raman scattering process involving electronic states of 2D surfaces. 31 However, in the present case, it should be considered the graphene sensitization of the nanocrystalline titania matrix 32,33 ; silica with exfoliated graphene (green); titania (red); and titania with exfoliated graphene thermally treated at 350°C in air (orange) and 3h at 400°C and further 2h at 450°C under inert atmosphere (blue). b) Bar plots showing the analytical enhancement factors (AEFs) of Rh6G for mesoporous films embedding exfoliated graphene with respect to bare mesoporous silica: silica treated for 2h at 450°C under inert atmosphere (green), titania treated for 2h at 350°C in air (orange) and titania treated for 2h at 450°C under inert atmosphere (anatase phase) with (blue) and without (red) embedded graphene.…”
Section: The Raman Spectra Inmentioning
confidence: 98%
“…Raman enhancement based on chemical mechanism in graphene has been explained as a resonant Raman scattering process involving electronic states of 2D surfaces. 31 However, in the present case, it should be considered the graphene sensitization of the nanocrystalline titania matrix 32,33 ; silica with exfoliated graphene (green); titania (red); and titania with exfoliated graphene thermally treated at 350°C in air (orange) and 3h at 400°C and further 2h at 450°C under inert atmosphere (blue). b) Bar plots showing the analytical enhancement factors (AEFs) of Rh6G for mesoporous films embedding exfoliated graphene with respect to bare mesoporous silica: silica treated for 2h at 450°C under inert atmosphere (green), titania treated for 2h at 350°C in air (orange) and titania treated for 2h at 450°C under inert atmosphere (anatase phase) with (blue) and without (red) embedded graphene.…”
Section: The Raman Spectra Inmentioning
confidence: 98%
“…graphene on the Raman signal of organic molecules. 3 It should be noted that this rather defective area of a sample was chosen for display and discussion due to its many interesting features, and that the quality of the graphene/1 films is usually much higher, without defects and with uniform coverage, as indicated in Figure 1c in the main manuscript.…”
Section: S3mentioning
confidence: 99%
“…Since the isolation of single layer graphene by mechanical exfoliation 1 and the subsequent discovery and demonstration of its outstanding electronic 2 and mechanical 3 properties, graphene has attracted an extremely high level of interest. It has been proposed for numerous applications in electronics, 4 photonics, [5][6] sensing, 7 as well as gas barriers 8 and coatings.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that GERS exhibits high molecular sensitivity and selectivity, the enhancement depends on the probed molecular vibrational mode, and the Fermi energy of graphene . A theoretical framework that covers all the experimentally observed phenomena was proposed in 2014 . Due to its molecular sensitivity and selectivity, GERS was also suggested for applications in chemical and biological sensing devices …”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to expect that for strongly functionalized graphene the conditions for GERS will no longer be fulfilled, because the electronic states (that are also sensitive to sp 3 defects in graphene) are a critical factor in the GERS mechanism. [5,8,9] Graphene with defects has been already studied as a substrate for GERS. It was shown for ozone-treated graphene that for a mild oxidation of graphene the enhancement increased due to p-doping of graphene.…”
Section: Introductionmentioning
confidence: 99%